2013
DOI: 10.1007/s12094-013-1142-x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of pathological response in colorectal cancer liver metastases following treatment with bevacizumab

Abstract: Pathological response may be a better indicator of treatment efficacy than RECIST for patients with mCRC receiving bevacizumab in the neoadjuvant setting. Adding bevacizumab to chemotherapy has the potential to increase pathological response rates. Well-designed prospective clinical studies are required to establish the efficacy and tolerability of this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…[12] Compared to chemotherapy alone, the addition of bevacizumab improved liver metastases response rate. [3,13,14] In the present study, we evaluated the response of colorectal metastases by using imaging technology and confirmed that the addition of bevacizumab can lead to higher response rate compared with preoperative chemotherapy alone (59.4% vs 38.6%). For patients with initially unresectable liver metastases, a strong correlation between response rate and resection rate in neoadjuvant treatment of mCRC was demonstrated.…”
Section: Discussionsupporting
confidence: 60%
“…[12] Compared to chemotherapy alone, the addition of bevacizumab improved liver metastases response rate. [3,13,14] In the present study, we evaluated the response of colorectal metastases by using imaging technology and confirmed that the addition of bevacizumab can lead to higher response rate compared with preoperative chemotherapy alone (59.4% vs 38.6%). For patients with initially unresectable liver metastases, a strong correlation between response rate and resection rate in neoadjuvant treatment of mCRC was demonstrated.…”
Section: Discussionsupporting
confidence: 60%
“…Based on our pooled results, we find that NCT plus bevacizumab could employ a role in the neoadjuvant setting for CRLM patients in particular in terms of ORR and R0 hepatic resection rate, while comparable efficacy is found between NCT plus EGFR-MoAbs and NCT alone in terms of hepatic resection rate and R0 hepatic resection rate. Additionally, several retrospective studies have demonstrated that the addition of bevacizumab to chemotherapy in the neoadjuvant and conversion setting significantly improve pathological response in CRLM patients, and patients with a good pathological response to neoadjuvant chemotherapy are associated with a better outcome [ 41 , 55 , 56 ]. Based on these encouraging data, the combination of NCT plus bevacizumab as neoadjuvant and conversion therapy could be recommended for initially unresectable or resectable CRLM patients due to its higher ORR and R0 hepatic resection rate.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relevance of the cytotoxic backbone added to preoperative bevacizumab is yet unclear, recent data seem to indicate that the optimization of the associated regimen could impact bevacizumab-induced increase in pathologic response rate [47]. Moreover, bevacizumab had been shown to improve the degree of pathological response [48], and to induce an unusual, infarct-like necrosis [49]; both conditions have been reported to be associated with better prognosis [18]. In practice, however, no imaging technique is able to predict preoperatively the achievement of complete pathological response, despite the complete radiologic response on diagnostic imaging [23,50,51].…”
Section: Which Is the Effect Of Bevacizumab On The Pathology Of Livermentioning
confidence: 99%